Extrapolation in the development of paediatric medicines: examples from approvals for biological treatments for paediatric chronic immune-mediated inflammatory diseases. Issue 10 (29th May 2017) - Stefanska, Anna M; Distlerová, Dorota; Musaus, Joachim; Olski, Thorsten M; Dunder, Kristina; Salmonson, Tomas; Mentzer, Dirk; Müller-Berghaus, Jan; Hemmings, Robert; Veselý, Richard
Abstract : The European Union (EU) Paediatric Regulation requires that all new medicinal products applying for a marketing authorisation (MA) in the EU provide a paediatric investigation plan (PIP) covering a clinical and non-clinical trial programme relating to the use in the paediatric population, unless a waiver applies. Conducting trials in children is challenging on many levels, including ethical and practical issues, which may affect the availability of the clinical evidence. In scientifically justified cases, extrapolation of data from other populations can be an option to gather evidence supporting the benefit–risk assessment of the medicinal product for paediatric use. The European Medicines Agency (EMA) is working on providing a framework for extrapolation that is scientifically valid, reliable and adequate to support MA of medicines for children. It is expected that the extrapolation framework together with therapeutic area guidelines and individual case studies will support future PIPs. Extrapolation has already been employed in several paediatric development programmes including biological treatment for immune-mediated diseases. This article reviews extrapolation strategies from MA applications for products for the treatment of juvenile idiopathic arthritis, paediatric psoriasis and paediatric inflammatory bowel disease. It also provides a summary of extrapolation advice expressed in relevant EMA guidelines and initiatives supporting the use of alternative approaches in paediatric medicine development.